Multifaceted quality improvement initiative to decrease pediatric asthma readmissions. (21st October 2017) - Krupp, Nadia L; Fiscus, Cindy; Webb, Russell; Webber, Emily C; Stanley, Teresa; Pettit, Rebecca; Davis, Ashley; Hollingsworth, Judy; Bagley, Deborah; McCaskey, Marjorie; Stevens, John C; Weist, Andrea; et al.
ABSTRACT: Background : Asthma is the most common chronic disease of childhood and a leading cause of hospitalization in children. A primary goal of asthma control is prevention of hospitalizations. A hospital admission is the single strongest predictor of future hospital admissions for asthma. The 30-day asthma readmission rate at our institution was significantly higher than that of other hospitals in the Children's Hospital Association. As a result, a multifaceted quality improvement project was undertaken with the goal of reducing the 30-day inpatient asthma readmission rate by 50% within two years. Methods : Analysis of our institution's readmission patterns, value stream mapping of asthma admission, discharge, and follow-up processes, literature review, and examination of comparable successful programs around the United States were all utilized to identify potential targets for intervention. Interventions were implemented in a stepwise manner, and included increasing inhaler availability after discharge, modifying asthma education strategies, and providing in-home post-discharge follow-up. The primary outcome was a running 12-month average 30-day inpatient readmission rate. Secondary outcomes included process measures for individual interventions. Results : From a peak of 7.98% in January 2013, a steady decline to 1.65% was observed by July 2014, which represented a 79.3% reduction in 30-day readmissions. Conclusion : A significant decrease in hospital readmissions for pediatric asthma is possible, through comprehensive, multidisciplinary quality improvement that spans the continuum of care.